2020
DOI: 10.3390/ijms21217975
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting the Formation and Treatment of Thrombosis by Natural and Synthetic Compounds

Abstract: Venous thromboembolism (VTE) refers to deep vein thrombosis (DVT), whose consequence may be a pulmonary embolism (PE). Thrombosis is associated with significant morbidity and mortality and is the third most common cardiovascular disease after myocardial infarction and stroke. DVT is associated with the formation of a blood clot in a deep vein in the body. Thrombosis promotes slowed blood flow, hypoxia, cell activation, and the associated release of many active substances involved in blood clot formation. All t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 296 publications
0
25
0
1
Order By: Relevance
“…Thus, the increase in cardiovascular incidents requires the introduction of natural anticoagulants that would be effective in treating and preventing thrombosis without affecting hemostasis. Various substances of natural origin influence the mechanisms of thrombosis in diverse ways, affecting the coagulation system and platelet activation and aggregation [ 38 ]. Astragalin inhibited cigarette smoke-induced PAR signaling in lung tissues, indicating that this compound may deter thrombin activity and ensuing pulmonary thromboembolism.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, the increase in cardiovascular incidents requires the introduction of natural anticoagulants that would be effective in treating and preventing thrombosis without affecting hemostasis. Various substances of natural origin influence the mechanisms of thrombosis in diverse ways, affecting the coagulation system and platelet activation and aggregation [ 38 ]. Astragalin inhibited cigarette smoke-induced PAR signaling in lung tissues, indicating that this compound may deter thrombin activity and ensuing pulmonary thromboembolism.…”
Section: Discussionmentioning
confidence: 99%
“…As expected, astragalin suppressed thrombin-stimulated alveolar induction of PAR proteins and enhanced tPA induction along with concurrent reduction of PAI-1. Since oxidative stress promotes thrombosis [ 39 ], natural compounds that reduce the level of oxidative stress may be candidates for treating thrombotic complications [ 38 , 40 ]. This study found that astragalin inhibited thrombin-induced ROS production and ensuing MAPK signaling, which would be a safe and effective novel antithrombotic pharmacotherapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Venous thromboembolism (VTE) is a medical condition that includes deep vein thrombosis (DVT) and pulmonary embolism (PE) [1,2]. Orthopedic surgery of the lower limbs constitutes a high-risk factor for VTE: patients undergoing total hip and knee arthroplasty show an incidence of this complication of approximately 0.6-1.5% [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Since diabetes, hypertension and cardiovascular disease are additional risk factors for thrombosis that is also associated to oxidative stress, the dietary supplement with natural compounds such as flavonoids, isoflavonoids, and terpenoids might be useful to reduce the risk of thrombosis reducing ROS levels and pro-inflammatory cytokines; in addition, they exercise anticoagulant effects, probably via the endogenous coagulation system and thus inhibit platelet aggregation/function or prothrombotic effects [ 13 ].…”
mentioning
confidence: 99%